2022
DOI: 10.1038/s41536-022-00220-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanically and biochemically functional scaffold for recruitment of endogenous stem cells to promote tendon regeneration

Abstract: Tendon regeneration highly relies on biomechanical and biochemical cues in the repair microenvironment. Herein, we combined the decellularized bovine tendon sheet (DBTS) with extracellular matrix (ECM) from tendon-derived stem cells (TDSCs) to fabricate a biomechanically and biochemically functional scaffold (tECM-DBTS), to provide a functional and stem cell ECM-based microenvironment for tendon regeneration. Our prior study showed that DBTS was biomechanically suitable to tendon repair. In this study, the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Because the body structure of nonhuman primates is closer to that of humans, 3D-CH-IB-ST needs to be implanted in the TBI model of non-human primates to evaluate the effect of 3D-CH-IB-ST on TBI repair before clinical trials. It is worthwhile to perform further research on the modification of chemical cross-linking and the enhancement of physical qualities in the creation of scaffolds [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Because the body structure of nonhuman primates is closer to that of humans, 3D-CH-IB-ST needs to be implanted in the TBI model of non-human primates to evaluate the effect of 3D-CH-IB-ST on TBI repair before clinical trials. It is worthwhile to perform further research on the modification of chemical cross-linking and the enhancement of physical qualities in the creation of scaffolds [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Deeken et al, 10 in 2011, reported that decellularization using tri (n‐butyl) phosphate (1%) was found to be more effective in decellularization than other chemicals, including peracetic acid, sodium dodecyl sulfate, and so forth, preserving the structure and ECM composition intact. Receullarisation approaches using decellularized bovine tendon sheets with ECM from tendon‐derived stem cells to fabricate biomechanically and biochemically functional scaffolds providing a microenvironment for tendon regeneration 11 and preclinical trials in rat models using decellularized scaffolds 12 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Receullarisation approaches using decellularized bovine tendon sheets with ECM from tendon-derived stem cells to fabricate biomechanically and biochemically functional scaffolds providing a microenvironment for tendon regeneration 11 and preclinical trials in rat models using decellularized scaffolds 12 have been reported.…”
mentioning
confidence: 99%
“…Decellularized tendon scaffolds have great potential for tendon repair [ 9 ]. They have been shown to maintain the tissue biomechanical properties and composition, including tendon-specific structural proteins, growth factors, and cytokines [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized tendon scaffolds have great potential for tendon repair [ 9 ]. They have been shown to maintain the tissue biomechanical properties and composition, including tendon-specific structural proteins, growth factors, and cytokines [ 9 , 10 ]. However, for their clinical application, decellularized tendon scaffolds still have many drawbacks, such as cell source, ex vivo regeneration [ 11 ], limited shapes, and donor shortage.…”
Section: Introductionmentioning
confidence: 99%